Accuracy of QT interval measurement on electrocardiographs displayed on electronic 'smart' devices. (2nd February 2016) - Rotella, Joe‐Anthony; Taylor, David McD; Wong, Anselm; Greene, Shaun L
Abstract: Objective: The objective of the study was to compare QT intervals measured on the original bedside electrocardiographs (ECG), facsimile, iPhone, iPad and 17 inch computer monitor. Methods: This was a prospective, observational study conducted within a tertiary referral metropolitan ED. Thirteen doctors measured the QT intervals of 15 non‐identifiable, routinely recorded ECGs using randomly allocated modalities over five sessions. The QT intervals of lead I, II, V2, V4, V6 and one other were measured. Variations between modalities and between doctors were examined (χ 2 and Kruskal–Wallis tests). Results: QT intervals measured on the iPad were significantly lower than the other modalities ( P  = 0.02). For each lead, there were no differences in QT interval measurement between the modalities ( P  > 0.05). However, there were significant differences between the QT interval measurements of the participating doctors (range of median QT intervals 480–530 msec, P  < 0.001). There were also significant differences between the QT intervals measurement of the leads examined (range of median QT intervals 480–520 msec, P  < 0.001). Lead V2 was the most consistent lead (smallest interquartile range), and lead I was the least (QT interval consistently under‐estimated). Conclusion: The QT interval can be reliably measured using facsimile, iPhone and computer, but not the iPad. However, it varies between doctors. Lead V2 is recommended for QT interval measurement if only a single lead is to be used for clinical purposes.